Demographic characteristics, home food environmental factors, nutritional status, and diet quality of Filipino adolescents from middle-income families in Quezon City, Philippines - Ambrocio, Jenessa Elesse M.; Dayrit, Allyson Marie C.; Sambile, Janine Anne M.; Callanta, Luz Felicidad S. (Quezon City University of the Philippines Diliman, 2023)
The home food environment is one of the many influences that affect adolescents' nutritional status and diet quality. This descriptive-correlational study aims to assess the relationship between demographic characteristics and the three home food environment factors - individual, social, and environmental - with nutritional status and diet quality in a sample of 120 middle-income parent-adolescent dyads in Quezon City, Philippines. The results of the study will increase Filipino families’ awareness of the vital role of the home food environment in shaping adolescents’ nutritional status and diet quality. A non-probability quota sampling method was used to select participants: Filipino adolescents (12-18 years old) and their parents (20-59 years old). Participant recruitment took place online with a set of inclusion and exclusion criteria that were followed. Data collection was conducted through two Google Forms. The first form collected the participants’ contact and demographic information. The second form collected the adolescents’ anthropometric data, the participants’ perceptions of their home food environment, and their usual food consumption. Responses from each eligible dyad were included in the analyses of data using the Jamovi Statistical Software. Descriptive statistics were calculated to summarize the variables to determine the participants’ demographic characteristics and nutritional status, and measure their perceived home food environment factors and diet quality. Ultimately, the study reveals that there is generally a very weak relationship between the participants’ demographic characteristics and perceived home food environment factors, and the nutritional status and diet quality of Filipino adolescents from middle-income families in Quezon City, Philippines.
Thesis
Includes bibliographical references (pages 102-125)
Keywords: Teenagers -- Philippines -- Quezon City -- Nutrition; Teenagers -- Philippines -- Quezon City -- Food; Middle class families -- Philippines -- Quezon City; Family demography -- Philippines -- Quezon City